Clinical Features on Sensory Dysfunction of Upper Limbs of Patients with Unilateral Stroke - SHAO Peng; JIA Jie (康复学报, 2022)
ObjectiveTo analyse the clinical features on sensory dysfunction of upper limbs of patients with unilateral stroke by sensory function assessment.MethodsA total of 122 patients with unilateral stroke treated in five hospitals (including Jing'an District Hospital of Huashan Hospital Affiliated to Fudan University, etc.) were divided into cerebral infarction group and cerebral hemorrhage group according to the type of stroke, and the sensory function of both groups was evaluated respectively. The sensory function assessment mainly included superficial sensations (pinprick, temperature and tactile sensation), deep sensations (position sensation, kinesthesia and vibration), and complex sensations (tactile localization, stereognosis and two-point discrimination).Results(1) The distribution of different types of sensory impairment: the most common sensory impairments in patients with unila-teral stroke were the combination of superficial sensation impairments, deep sensation impairments, and complex sensations impairments (58.20%); the incidence of tactile sensation impairment was the highest (83.61%). (2) Types of sensory dysfunction: compared with the cerebral infarction group, the incidence of different types of sensory dysfunction was lower in the cerebral hemorrhage group, and some patients in the cerebral infarction group had no sensory impairment. There were statistically significant differences in the types of sensory dysfunction between the two groups (P<0.001). (3) Severity of sensory disorders: compared with the cerebral infarction group, the sensory impairments in pinprick, temperature, tactile sensation, position sensation, kinesthesia, vibration, tactile localization, stereognosis and two-point discrimination of the cerebral hemorrhage group were more serious.ConclusionThe inhibitory symptoms of upper limb sensory dysfunctions were more common in stroke patients, while the stimulating symptoms were relatively less; the patients with stroke often suffered from deep, superficial and complex sensory function impairments. There were differences in the occurence of different kinds of sensory impairment, with the superficial sensations more easily damaged in patients with unilateral stroke, while the deep sensations relatively less damaged; there were more types of sensory impairment in the cerebral infarction group, but with relatively less severity. There were fewer types of sensory impairment in the cerebral hemorrhage group, but the degree of sensory impairment was more serious than that of the cerebral infarction group.